2021
DOI: 10.3390/ani11051423
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Skeletal Muscle Reveals Candidate Genes Influencing Muscle Growth and Associated Lipid Composition in Portuguese Local Pig Breeds

Abstract: Gene expression is one of the main factors to influence meat quality by modulating fatty acid metabolism, composition, and deposition rates in muscle tissue. This study aimed to explore the transcriptomics of the Longissimus lumborum muscle in two local pig breeds with distinct genetic background using next-generation sequencing technology and Real-Time qPCR. RNA-seq yielded 49 differentially expressed genes between breeds, 34 overexpressed in the Alentejano (AL) and 15 in the Bísaro (BI) breed. Specific slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 105 publications
(122 reference statements)
2
13
0
Order By: Relevance
“…As found in other studies [ 38 , 124 ], differences tend to be more notable with the RNA-seq approach than with the Real-Time qPCR. However, the concordance correlation coefficient (CCC) showed an acceptable correlation between techniques (CCC in all samples = 0.73; CCC in females = 0.66; CCC in males = 0.60).…”
Section: Resultssupporting
confidence: 75%
“…As found in other studies [ 38 , 124 ], differences tend to be more notable with the RNA-seq approach than with the Real-Time qPCR. However, the concordance correlation coefficient (CCC) showed an acceptable correlation between techniques (CCC in all samples = 0.73; CCC in females = 0.66; CCC in males = 0.60).…”
Section: Resultssupporting
confidence: 75%
“…Additionally, fatty acid metabolism strongly influences meat quality. Previous studies have found that the fatty acid composition and its metabolism in muscles are important factors influencing overall meat quality and consumer preference ( 15 , 33 – 35 ). In the present study, enrichment analysis of the muscle metabolomic data revealed several pathways related to fat metabolic processes ( Figures 4 , 6 ), including arachidonic acid metabolism and fatty acid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-omics techniques are widely used to analyze muscle tissue in sheep, pigs and cattle and have identified many genes involved in fatty acid metabolism (11)(12)(13)(14). RNA-seq and qRT-PCR have identified several candidate genes for lipid metabolism, such as ACLY, ADIPOQ, ELOVL6, LEP and ME1, as main gene factors defining the processes influencing meat composition and quality (15).…”
Section: Introductionmentioning
confidence: 99%
“…In response to carbohydrate intake, glucose is taken by adipocytes through insulin-stimulated GLUT4 (see Figure 2 ). There are several published schematic representations of the pathways involved in de novo fatty acid synthesis [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. A simplified pathway is shown in Figure 2 .…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%
“…Poklukar et al [ 46 ] published a detailed review on the transcriptomic networks, hormones and enzymes modulating transcriptional regulation of adipogenesis in local and modern pig genotypes. Additionally, other studies have also revealed putative IMF accretion and fat metabolism-related genes [ 45 , 46 , 47 , 48 , 49 ], hormones, enzymes, transcription factors, and miRNAs [ 50 , 51 , 52 ] and their interaction with dietary nutrients [ 2 , 12 , 53 , 54 ] in pigs. Other findings evinced the possible association of genes influencing fat deposition and IMF accretion to the mitogen-activated protein kinase (MAPK) pathway regulating adipogenesis and lipogenesis [ 55 , 56 ].…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%